Evolution of Non‐Metallic Inclusions from FeTi70R Alloys during Alloying of Fe–40Ni–20Cr Steels. Issue 11 (7th April 2016) - Kellner, Hans E.O.; Karasev, Andrey V.; Memarpour, Arashk; Jönsson, Pär G.
Abstract : In this study, the composition, size, and number of large non‐metallic inclusions (>20 μm) are investigated in a commercial refined FeTi70R alloy, which is used for deoxidation and alloying of different industrial high‐quality steels. It is found that this ferroalloy contains different complex oxide inclusions, which sizes vary from 20 to 260 μm. These different complex inclusions contain mostly CaO, SiO2, and TiO x . When adding FeTi70R alloy in the steel during the final stage of ladle treatment, these large size inclusions can significantly decrease the cleanliness and mechanical properties of steel. Therefore, the evolution and behavior of these inclusions after addition of this ferroalloy into the liquid iron or Fe–40Ni–20Cr steel are investigated in laboratory experiments. In addition, the results from the laboratory scale experiments are compared to results obtained from industrial heats using Alloy 825. A consideration of the evolution mechanism of large inclusions after an addition of a FeTi70R alloy helps to understand their behavior in the melt. It also helps to estimate their possible harmful effects on the quality of this steel grade during commercial production. Abstract : To understand how FeTi70R affects Ni‐based alloys, the macro inclusions in FeTi70R are investigated. Laboratory experiments are performed to see how these inclusions evolve in the melt and how different parameters affect their evolution. Industrial samples are taken to confirm if these inclusions exist during production and if they affect the quality.